ZChicken as a mustahik economic empowerment program by BAZNAS: A qualitative analysis - M Fatchurrohman; Silvy Meilaeni Asifa (Department of Islamic Economics, Islamic University of Indonesia, 2023)
IntroductionBAZNAS has launched numerous economic empowerment programs for mustahik. One of the programs that has been introduced is ZChicken, which focuses on the sale of crispy fried chicken. However, there is still a limited amount of research available on ZChicken.ObjectivesThis study aims to analyze ZChicken as an economic empowerment program for mustahik from various perspectives, including its development, the need for halal certification, and the achievements obtained.MethodThis study employed a qualitative approach to analyze the ZChicken program as an economic empowerment initiative for the mustahik by BAZNAS. The research methodology employed in this study involved conducting a content analysis of ZChicken-related materials on the BAZNAS website as well as other news websites.ResultsThe result shows that BAZNAS introduced the ZChicken as an empowerment program in the culinary sector that revolves around a fried chicken franchise concept. ZChicken has been received well in the society, has been certified halal, and has its own brand.ImplicationsBAZNAS needs to maintain quality program in ZChicken to ensure trust among muzakki and the society. ZChicken should maintain its halal and brand certification by monitoring and supervision from BAZNAS.Originality/NoveltyThis study provides insights on how ZChicken as an economic empowerment program from BAZNAS has grown to be a successful force for empowering mustahik in many locations.